Influence of Injection Drug Use–Related HIV Acquisition on CD4 Response to First Antiretroviral Therapy Regimen Among Virally Suppressed Individuals. (1st March 2018) - Calkins, Keri L.; Lesko, Catherine R.; Chander, Geetanjali; Moore, Richard D.; Lau, Bryan
Abstract : Background: The inflammatory effects of injection drug use (IDU) may result in an impaired immune response to antiretroviral therapy (ART). We examined CD4 response to first ART regimen among individuals in routine HIV care, stratified by IDU-related HIV acquisition. Setting: Cohort study including patients who initiated ART between 2000 and 2015 in the Johns Hopkins HIV Clinic. Methods: We followed individuals from ART initiation until death, loss to follow-up, loss of viral load suppression (<500 copies/mL), or administrative censoring. We described CD4 trajectories after ART initiation using inverse probability weighted quantile regression models with restricted cubic splines for time. Weights accounted for differences in baseline characteristics of persons comparing those with IDU-related HIV acquisition to those with other HIV acquisition risks (non-IDU) and possible nondifferential censoring due to death, loss to follow-up, or loss of viral load suppression. We also examined CD4 response by strata of CD4 at ART initiation (⩽200, 201–350, >350). Results: Of 1244 patients initiating ART, 30.4% were IDU. Absolute CD4 cell difference at the 50th percentile comparing IDU with non-IDU was −25 cells [95% confidence interval (CI): −63 to 35], −66 cells (95% CI: −141 to 16), and −91 cells (95% CI: −190 to −5) at 2, 4, and 6 years after ART initiation, respectively. Results were similar (non-IDU with slightly higher CD4 count, but not statistically significant differences) at other percentiles and stratified by baseline CD4. Conclusions: CD4 recovery after ART initiation was similar for IDU and non-IDU, conditional on consistent viral load suppression.